(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
A small group of features, two of which were definitely prehistoric in date are described and discussed. Associated artefacts included a small assemblage of Neolithic lithics, prehistoric pottery, a boulder quern and two cobble tools. A small single-storey building of 18th century construction with two phases is thought to have been a worker’s cottage of uncertain function. Several pits and postholes of comparable date were also excavated. There are specialist reports on pottery, ceramic building material, clay pipes, glass, gunflint, gunstone, metalwork and animal bone.